Indications for and Findings on Transthoracic Echocardiography in COVID-19 patients admitted to a Tertiary Care Government Medical Hospital. (March 2022) - Sayed, M.A.; Guru, N.K.; Syed, H.; Nazneen, S.; Jaffery, S.; Soomro, A.; Khan, A.; Begum, S.; Sayed, S.A.
Abstract : Purpose: We aimed to document the performance of transthoracic echocardiography (TTE) and the spectrum of echocardiographic findings as complications associated with coronavirus disease 2019 (COVID-19). Methods & Materials: A retrospective analysis was performed among adult patients admitted to a tertiary care government hospital in Maharashtra between January 01, 2021 and May 31, 2021. Patients were included if they underwent TTE during the hospitalization after a known positive diagnosis for COVID-19. Demographic and clinical data were obtained using chart abstraction from the medical record system. Results: Of 1539 patients, 187 (12.15%) underwent TTE following positive results on severe acute respiratory syndrome coronavirus-2 polymerase chain reaction testing. The most common clinical indications for TTE were concern for a major acute cardiovascular event (52.95%) and hemodynamic instability (32.29%). Although most patients had preserved biventricular function, 41.30% were found to have left ventricular ejection fractions ≤ 50%, and 13.9% had at least moderately reduced right ventricular function. Eleven patients had wall motion abnormalities suggestive of stress-induced cardiomyopathy. Using Spearman rank correlation, there was an inverse relationship between high-sensitivity troponin T and left ventricular ejection fraction (ρ = -0.41, P < 0.01). Amongst 37 patients with prior echocardiograms, only seven (18.91%) had new reductions in LVEF of >10%. Clinical management was changed in seventeen individuals (26.98%) in whom TTE was ordered for concern for acute major cardiovascular events and seven (14.58%) in whom TTE was ordered for hemodynamic evaluation. Conclusion: Our study describes the clinical indications for use and diagnostic performance of TTE, as well as findings seen on TTE, in hospitalized patients with COVID-19. In appropriately selected patients, TTE can be an invaluable tool for guiding COVID-19 clinical management.